2023
DOI: 10.21203/rs.3.rs-2482695/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I just get scared it’s going to happen again”: A qualitative study of the psychosocial impact of pediatric burns from the child’s perspective

Abstract: Background Advances in medicine have improved the chances of survival following burn injuries, however, psychosocial outcomes have not seen the same improvement, and burn injuries can be distressing for both the child or young person, negatively affecting their wellbeing. Pediatric burn patients are at a higher risk of developing psychopathology compared to the general population. In order to promote resilience and prevent psychopathology post-burn injury for pediatric burn patients, it is crucial to understa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
4
Order By: Relevance
“…Die körperlichen Beeinträchtigungen bilden zudem ein Risiko für das Größen-und Gewichtswachstum sowie für die Fähigkeit zur Teilnahme an organisierten Aktivitäten und den Einfluss auf soziale Interaktionen [9]. Kinder und Jugendliche mit Verbrennungen wiesen unter anderem eine hohe Rate an Angstzuständen, PTBS, Depressionen und kognitiven Schwierigkeiten sowie eine geringe Zufriedenheit mit dem Körperbild auf [3][4] [9][10][11][12]. Ebenfalls wurde bei betroffenen Eltern von vermehrten Angstsymptomen und traumatischem Stress sowie darüber berichtet, dass sie mit ihren Kindern emotional und psychisch mitleiden, Schuldgefühle und Scham entwickeln sowie ihre eigenen Bedürfnisse zurückstecken [4][9] [10] [12] [13].…”
Section: Nachfolgende Auswirkungen Der Brandverletzungunclassified
“…Die körperlichen Beeinträchtigungen bilden zudem ein Risiko für das Größen-und Gewichtswachstum sowie für die Fähigkeit zur Teilnahme an organisierten Aktivitäten und den Einfluss auf soziale Interaktionen [9]. Kinder und Jugendliche mit Verbrennungen wiesen unter anderem eine hohe Rate an Angstzuständen, PTBS, Depressionen und kognitiven Schwierigkeiten sowie eine geringe Zufriedenheit mit dem Körperbild auf [3][4] [9][10][11][12]. Ebenfalls wurde bei betroffenen Eltern von vermehrten Angstsymptomen und traumatischem Stress sowie darüber berichtet, dass sie mit ihren Kindern emotional und psychisch mitleiden, Schuldgefühle und Scham entwickeln sowie ihre eigenen Bedürfnisse zurückstecken [4][9] [10] [12] [13].…”
Section: Nachfolgende Auswirkungen Der Brandverletzungunclassified
“…For example, children with certain medical conditions, such as epilepsy or developmental disabilities, may be more prone to accidents and injuries, including burns [8]. Furthermore, studies have shown that children who have experienced a burn injury are at a higher risk of developing psychopathology, such as post-traumatic stress symptoms or post-traumatic stress disorder (PTSD) [9].…”
Section: Causes and Risk Factors For Pediatric Burnsmentioning
confidence: 99%
“…Te location of the burn can impact the functional and cosmetic outcomes of the injury. For example, burns on the hands or face may result in functional impairments and require specialized care and rehabilitation [9]. In addition, the severity and prognosis of pediatric burn injuries can be classifed based on factors such as the presence of an inhalation injury, comorbidities, and the risk of infection.…”
Section: Classification Of Burnsmentioning
confidence: 99%
See 2 more Smart Citations